Never split the difference : negotiating as if your life depended on it - Voss, Chris (Negotiator) (New York : HarperBusiness, an imprint of HarperCollins Publishers, 2016)
"A negotiation guide from a former FBI Hostage Negotiator"--
Keywords: Negotiation; Negotiation in business; BUSINESS & ECONOMICS / Negotiating; BUSINESS & ECONOMICS / Business Communication / General